2018
DOI: 10.1080/02640414.2018.1446386
|View full text |Cite
|
Sign up to set email alerts
|

Lower leg and foot contributions to turnout in female pre-professional dancers: A 3D kinematic analysis

Abstract: Turnout is a central element of classical ballet which involves sustained external rotation of the lower limbs during dance movements. Lower leg and foot compensation mechanisms which are often used to increase turnout have been attributed to the high incidence of lower limb injury in dancers. Evaluation of dancers' leg posture is needed to provide insight into the lower limb kinematic strategies used to achieve turnout. The primary purpose of this study was to use 3D kinematic analyses to determine the lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Participants wore tight-fitting spandex clothes, and 16 reflective markers were placed bilaterally on participants’ feet, legs, and thigh and around the pelvis according to Plug-in-Gait lower body model guidelines (Vicon, Centennial, Colorado, USA). Three-dimensional lower extremity marker position data were collected using a 10-camera motion capture system (Vicon, Vantage V8, Centennial, Colorado, USA) sampling at 250 Hz 28,29. GRF and moment data were collected using two in-ground force plates (Advanced Mechanical Technology Inc., Waterton, MA, USA) sampling at 1000 Hz 27…”
Section: Methodsmentioning
confidence: 99%
“…Participants wore tight-fitting spandex clothes, and 16 reflective markers were placed bilaterally on participants’ feet, legs, and thigh and around the pelvis according to Plug-in-Gait lower body model guidelines (Vicon, Centennial, Colorado, USA). Three-dimensional lower extremity marker position data were collected using a 10-camera motion capture system (Vicon, Vantage V8, Centennial, Colorado, USA) sampling at 250 Hz 28,29. GRF and moment data were collected using two in-ground force plates (Advanced Mechanical Technology Inc., Waterton, MA, USA) sampling at 1000 Hz 27…”
Section: Methodsmentioning
confidence: 99%
“…Studies with kinematics evaluations of dancers with and without low back pain, that is, assessments of the articular movement of the lumbosacral spine and the hip joint, show that pain does not influence the joint mobility of the spine of dancers with low back pain [ 22 , 23 ]. Studies on ankle kinematics [ 20 ] observed that a significant decrease in the height of the medial longitudinal arch can induces decreases in the body stability during landing in jumping movements [ 46 ]. Thus, the foot support base is a main key point for integrating greater body stability and balance for dancers [ 7 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of changes in foot posture, leads to understanding of other factors, such as the intrinsic and extrinsic muscle strength of the foot [ 46 ], which in turn may be related to the time of practice and frequency of training, given that mild low back pain promoted a supine foot posture, while moderate and high levels promoted a neutral foot posture. According to Carter et al [ 20 ], dancers are more likely to pronate their foot than rotate their knee to compensate for limited external hip rotation. Dancers with limited foot pronation ability may force additional rotation through the knee [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate turnout should be accomplished by external rotation of hip joint [16]. When the angle of hip external rotation is insufficient, turnout is often augmented by other joints in the lower extremity and lumbar region along the kinematic chain [15,17,18]. In such forced turnout, there is hyperpronation of subtalar joints, called "rolling in."…”
Section: Introductionmentioning
confidence: 99%